Collective action and property rights in fisheries management - Ahmed, Mahfuzuddin; Viswanathan, K. Kuperan; Valmonte-Santos, Rowena (International Food Policy Research Institute, 2004)
Fisheries are complex and interdependent ecological and social systems that require integrated management approaches. The actions of one person or group of users affect the availability of the resource for others. Managing such common pool resources requires conscious efforts by a broad range of stakeholders to organize and craft rules enabling equitable and sustainable use of the resources for everyone?s benefit. Collective action is often a prerequisite for the development of community-based institutions and the devolution of authority... in the 1990s the WorldFish Center conducted an issuebased, multisectoral, and multidisciplinary analysis (including ecological, economic, social, political, and administrative perspectives) that led to the production of a coastal environmental profile, a technical report detailing the status of fisheries, and an integrated fisheries management plan.... San Miguel?s experience highlights (1) the critical role of an appropriate human perception of the situation; (2) the importance of collective action and stakeholder participation at key stages of research, planning, and implementation; (3) the usefulness of structured decision methods for research, planning, and associated debates; and (4) the efficacy of research combined with planning efforts to ensure its utilization and relevance on the one hand and to provide a scientific basis for management planning on the other. --- from Text.